2016
DOI: 10.1073/pnas.1612736113
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer tumorigenicity is dependent on high expression levels of NAF-1 and the lability of its Fe-S clusters

Abstract: Iron-sulfur (Fe-S) proteins are thought to play an important role in cancer cells mediating redox reactions, DNA replication, and telomere maintenance. Nutrient-deprivation autophagy factor-1 (NAF-1) is a 2Fe-2S protein associated with the progression of multiple cancer types. It is unique among Fe-S proteins because of its 3Cys-1His cluster coordination structure that allows it to be relatively stable, as well as to transfer its clusters to apo-acceptor proteins. Here, we report that overexpression of NAF-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
130
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 38 publications
3
130
0
Order By: Relevance
“…Biological studies confirmed our initial proposals and led to the hypothesis that the NEETs participate in the regulation of different iron, Fe-S, and reactive oxygen/redox reactions in cells (2,13). Indeed, NEET proteins play a key role in many cellular functions, as well as in different human diseases (2,6,(13)(14)(15)(16)(17)(18).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Biological studies confirmed our initial proposals and led to the hypothesis that the NEETs participate in the regulation of different iron, Fe-S, and reactive oxygen/redox reactions in cells (2,13). Indeed, NEET proteins play a key role in many cellular functions, as well as in different human diseases (2,6,(13)(14)(15)(16)(17)(18).…”
supporting
confidence: 64%
“…Also known as CDGSH proteins, due to their signature [2Fe-2S]-binding domain consensus sequence [C-X-C-X2-(S/T)-X3-P-X-C-D-G-(S/A/T)-H], these proteins are highly conserved from bacteria to humans (3). The 3Cys-1His cluster-binding site of NEET proteins houses a [2Fe-2S] redox-sensing cluster that can be transferred to apo-acceptor protein(s) when the cluster is oxidized (2,(4)(5)(6)(7). The [2Fe-2S] clusters of NEET proteins can also participate in electron transfer reactions (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Although AtNEET was found to be localized to the chloroplast (Nechushtai et al , ; Su et al , ), and the suppression of its expression was shown to cause impaired growth, early senescence, and the accumulation of Fe and ROS in Arabidopsis plants (Nechushtai et al , ), the function of AtNEET in relation to its localization and the phenotypes its suppression induced were unclear. Here we show that disrupting AtNEET function using a dominant‐negative strategy (Darash‐Yahana et al , ) impairs chloroplastic 2Fe–2S metabolism and causes the enhanced expression of many different transcripts involved in Fe‐deficiency responses, Fe–S biosynthesis in mitochondria, cytosol and chloroplasts, and Fe–S proteins (Figures and ). Proteomics analysis shows that despite the higher expression levels of transcripts encoding Fe–S proteins, the abundance of several Fe–S proteins, and in particular 2Fe–2S, in H89C plants is low (e.g.…”
Section: Discussionmentioning
confidence: 73%
“…By way of contrast, only the Cisd2 mKO mice showed significant mitochondrial dysfunction. Furthermore, previous studies have revealed that Cisd2‐deficient mouse embryonic fibroblasts (MEFs) exhibit increased levels of reactive oxygen species (ROS) and reactive nitrogen species (RNS) (Wiley et al., 2013), and that Cisd2 overexpression is able to protect cells from H 2 O 2 ‐induced oxidative stress and cell death using a breast cancer cell model (Darash‐Yahana et al., 2016). In this context, four DEPs that are related to the ROS response and redox regulation were pinpointed; these are involved in the “NRF2‐mediated oxidative stress response” and “glutathione redox reactions” pathways.…”
Section: Resultsmentioning
confidence: 99%